A Preliminary Study of Reproductive HealthEducation Model for Indonesian Migrant Workers - HudiWinarso; RenyI’tishom; Hanna T. Silitonga (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background:It is estimated that around 4.5 millions of Indonesians work abroad, and 70% of themarewomen, aged ranging from 18 to 35 years old. Mostly are employed in the domestic sector as housemaids.They are prone to exploitation, extortion, physical and sexual abuses, due to human trafficking. Up to present,there is no reproductive health education programmesfor Indonesian migrant workershas been established.Thereforeit is necessary to provide education modules on reproductive health for them, which targetsspecificeducation levels and socio-economic background.Methods: We evaluated the effectiveness of three models of reproductive health education on 24 Indonesianmigrant workers as subjects. The subjects were classified into 3 groups, 8 subjects for each group. GroupA received conventional model (modules without case), group B received moduleswith few cases givenalongside, and group C received modules with many cases added to the modules. The modules included: (1)Female and male reproductive organs, (2) Fertile window, menstruation, pregnancy and abortion, (3) Humansexuality and sexual abuse, (4) Sex educationand sexually transmitted infections. Each modulewere givenin the scheme of 4x120 minutes,twice every week. The evaluations were conducted using pre-test post-testdesign. The effectiveness of intervention was assessed by analysis of variance (ANOVA). Furthermore, wealso conducted focussed group discussion(FGD) regarding the models and modules of the training in thefifth week of the experiment.Results: There was a significant differences between subjects received module without case (Group A)compared to subjects received module with a few cases added (Group B)and modules with many casesadded (Group C) at a<0.05, while there was no significant differences between subjects received modulewith few cases (Group B) compared with many cases added (Group B vs Group C) compared to Group Aand Group B (a<0.05). Our results showed that modules with many cases added has the highest interventioneffect in the reproductive health education models.Conclusion: Our study concludes that the most effective model to builtcompetencies in reproductive healthfor Indonesian migrant worker is specific modules with many cases (Module C).